NaCl Induces Flavonoid Biosynthesis through a Putative Novel Pathway in Post-harvest Ginkgo Leaves - Ni, Jun; Hao, Juan; Jiang, Zhifang; Zhan, Xiaori; Dong, Lixiang; Yang, Xiuli; Sun, Zhehang; Xu, Wenya; Wang, Zhikun; Xu, Maojun (Frontiers in Plant Science, 2017)
The flavonoids in the extracts of Ginkgo leaves have been shown to have great medical value: thus, a method to increase the flavonoid contents in these extracts is of significant importance for human health. In the present study, we investigated the changes in flavonoid contents and the corresponding gene expression levels in post-harvest Ginkgo leaves after various treatments. We found that both ultraviolet-B and NaCl treatment induced flavonoid accumulation. However, gene expression analysis showed that the increases in flavonoid contents were achieved by different pathways. Furthermore, post-harvest Ginkgo leaves responded differently to NaCl treatment compared with naturally grown leaves in both flavonoid contents and corresponding gene expression. In addition, combined treatment with ultraviolet-B and NaCl did not further increase the flavonoid contents compared with ultraviolet-B or NaCl treatment alone. Our results indicate the existence of a novel mechanism in response to NaCl treatment in post-harvest Ginkgo leaves, and provide a technique to increase flavonoid content in the pharmaceutical industry.